PENGARUH KONTEN INSTAGRAM TERHADAP MINAT BELI KONSUMEN DAFFA SNACK - Suhartini, Titik (Jurnal Ekonomi dan Teknik Informatika, 2024)
Technological developments are closely related to progress in various fields. By using technological sophistication everything becomes practical, one of which is the marketing sector. This large coverage is not impossible, many business actors are starting to look at potential customers with online marketing. Writing using a survey method by asking several questions to respondents. Data collection techniques using observation, documentation, literature studies and surveys. The sample selection technique used was purposive sampling. Instrument test using validity test and reliability test. The data analysis technique used is multiple linear regression analysis using the IBM SPSS 24 application. The results of the research are that the content of photo messages has a positive and significant effect on purchase intention. Communication style has a positive and significant effect on purchase intention. The quality of information has a positive but not significant effect on purchase intention. There is a positive and significant influence between the content of the photo message, the style of communication and the quality of the information together on consumer buying interest. The influence of content in increasing purchase interest can be optimized by using Instagram Ads or paid advertisements